2003
DOI: 10.1177/10983007030050010501
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Video Self-Modeling on Spontaneous Requesting in Children with Autism

Abstract: Video self-modeling (VSM) is a promising intervention to teach new skills and improve the use of existing skills in young children with autism. VSM includes observation and imitation of one's self on videotape that records specific desirable child behaviors. The purpose of this study was to test the effectiveness of VSM for training young children with autism to make spontaneous requests in school settings. Four young children with autism participated. Experimental control was demonstrated using a multiple-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
111
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(120 citation statements)
references
References 8 publications
6
111
0
3
Order By: Relevance
“…In addition, maintenance results for Tuan and Sam showed that they both maintained the target behaviors over time. Sam's maintenance of all target behaviors in both the training setting and the classroom supports previous findings (Nikopoulos & Keenan, 2007;Wert & Neisworth, 2003) that video self-modeling is an effective intervention for maintaining acquired skills over time. Tuan maintained manding for preferred toy items to the peer and greeting behavior in both settings; however, he did not maintain toy comments or activity comments.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…In addition, maintenance results for Tuan and Sam showed that they both maintained the target behaviors over time. Sam's maintenance of all target behaviors in both the training setting and the classroom supports previous findings (Nikopoulos & Keenan, 2007;Wert & Neisworth, 2003) that video self-modeling is an effective intervention for maintaining acquired skills over time. Tuan maintained manding for preferred toy items to the peer and greeting behavior in both settings; however, he did not maintain toy comments or activity comments.…”
Section: Discussionsupporting
confidence: 71%
“…However, several studies failed to improve social initiation skills of all participants (Buggey, 2012;Wert & Neisworth, 2003). Researchers noted that these participants did not attend to the video and participants in Buggey (2012) study were three years old.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Video feedback consists of the participant watching non-edited videos of their own behavior and then co-reviewing it with the teacher to evaluate the behavior(s) and to discuss adjustments in future performance [11]. Video self-modeling has proven effective for spontaneous requesting of young children with autism to adults [12], vocal and physical initiations with typical peers in a playground setting [13] and social engagement [14] and social initiations with typical peers [15,16]. Evidence for video feedback has also been demonstrated to improve social initiations of children with autism.…”
Section: Introductionmentioning
confidence: 99%